ANALISIS KINERJA KEUANGAN PEMERINTAH KABUPATEN FLORES TIMUR - Tobi, Maria Regina; Idayati, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to assess the financial performance of the local government of East Flores district by using financial ratio analysis to the Local Government Budget of East Flores district in 2012-2014 fiscal years.This research is case study research and descriptive approach. The analysis which has been applied to analyze the local financial performance is independency ratio, fiscal decentralization level ratio, effectiveness ratio, efficiency ratio, and expenditure harmony ratio. Meanwhile, the calculation of share and growth, map of local financial capacity, and financial capability index has been applied to analysis the local financial capability.Based on the result of the analysis and the calculation of local financial performance, it can be concluded that the patterns of the correlation and the local independency level of East Flores district is in instructive criteria. The fiscal decentralization level of East Flores district is still low but the effectiveness level of local financial management of East Flores district can be stated quite effective and the efficiency level of local financial management of East Flores district can be stated less efficient. The expenditure harmony ratio describes that between direct expenditure and indirect spending has not balanced yet. Based on the result of the calculation and the analysis of local financial capability, it can be concluded that the condition of the financial capability of East Flores district has not ideal yet. It can be seen from the result of the calculation of share and growth which shows that the position of East Flores district is in the Quadrant II. The financial capability of East Flores district is in high category when it is considered from the result of the calculation of financial capability index of East Flores district.Keywords: local finance, financial ratio, local government budget, financial performance